2015
DOI: 10.1103/physrevc.91.051301
|View full text |Cite|
|
Sign up to set email alerts
|

Accurate nuclear radii and binding energies from a chiral interaction

Abstract: With the goal of developing predictive ab-initio capability for light and medium-mass nuclei, twonucleon and three-nucleon forces from chiral effective field theory are optimized simultaneously to low-energy nucleon-nucleon scattering data, as well as binding energies and radii of few-nucleon systems and selected isotopes of carbon and oxygen. Coupled-cluster calculations based on this interaction, named NNLOsat, yield accurate binding energies and radii of nuclei up to 40 Ca, and are consistent with the empir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
612
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 469 publications
(638 citation statements)
references
References 116 publications
(226 reference statements)
26
612
0
Order By: Relevance
“…We observe that all these deficiencies might be corrected by having extra short-range repulsion in the NN section of the Hamiltonian. Other approaches, such as global fittings of chiral NN+3N forces to include medium mass isotopes, also hold the promise to reach proper saturation [76]. In general, it is found that the current NN-N3LO interaction with cutoff at 500 MeV, augmented by the local 3NF-NNLO with a 400 MeV local cutoff, tends to stretch the single particle spectrum too much compared to data.…”
Section: Discussionmentioning
confidence: 99%
“…We observe that all these deficiencies might be corrected by having extra short-range repulsion in the NN section of the Hamiltonian. Other approaches, such as global fittings of chiral NN+3N forces to include medium mass isotopes, also hold the promise to reach proper saturation [76]. In general, it is found that the current NN-N3LO interaction with cutoff at 500 MeV, augmented by the local 3NF-NNLO with a 400 MeV local cutoff, tends to stretch the single particle spectrum too much compared to data.…”
Section: Discussionmentioning
confidence: 99%
“…In section 6, we will present MR-IMSRG results with one of the first new N N +3N interactions that resulted from these efforts, NNLO sat [26]. By taking select many-body data into account in the optimization procedure, the creators of NNLO sat were able to improve the interaction's saturation properties, allowing an accurate description of the ground-state energies and radii of 40,48 Ca [140,141].…”
Section: Interactions and Implementationmentioning
confidence: 99%
“…One of the first new interactions to come out of these efforts is NNLO sat by Ekström and collaborators [26]. As the name suggests, it is defined at chiral order NNLO, and contains N N and 3N interactions.…”
Section: Oxygen Isotopesmentioning
confidence: 99%
See 1 more Smart Citation
“…For symmetric matter it was found that low-momentum NN plus 3N interactions are capable to predict realistic saturation properties, with 3N forces fit only to few-body data [7], whereas neutron matter was found to be perturbative [8]. In subsequent studies, symmetric matter and neutron matter were also investigated based on chiral EFT interactions within the self-consistent Green's function framework [9,10], using coupled-cluster theory [11,12], with in-medium chiral perturbation theory [13] and in many-body perturbation theory [14]. Furthermore, the development of novel local chiral NN forces opened the way to first Quantum Monte Carlo studies of neutron matter based on chiral EFT interactions [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%